A Theology of Failure : Žižek against Christian Innocence - Rose, Marika (Book collections on Project MUSE., 2019)
This book draws the work of Slavoj Žižek into conversation with the Christian mystical theological tradition in order to propose a materialist account of Christian identity as constituted by failure.